People and parks: implications for sustainable development in the Thukela biosphere reserve, KwaZulu/Natal - Brinkcate, Therese Anne (My University, 2016)
South Africa has recently begun a number of conservation Initiatives which link conservation with the development of people This follows a worldwide trend in which it is acknowledged that conservation cannot be undertaker without the participation of local communities who are most affected by the establishment of protected areas The Thukela Biosphere Reserve In KwaZulu/Natal South Africa iS such an Initiative The research provides an assessment of the potential of the TBR to successfully introduce a sustainable land use strategy in the region This assessment is achieved through an investigation of the historical situation as well as local communities perceptions and attitudes toward the TBR and environmental degradation These attitudes are compared to a more scientific analysis of land degradation The research made use of participatory methodologies to assess these perceptions Findings indicate that local Afrrcan communities are intensely aware of environmental degradation in the TBR A number of factors however prevent them from accepting the TBR as an effective land use option These include oppressive historical polices leading[Abbreviated [ Abstract. Open document to view full version]
A dissertation submitted to the faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science Johannesburg 1997
Keywords: Biosphere reserves -- South Africa -- Kwazulu-Natal.; Sustainable development -- South Africa -- KwaZulu-Natal -- Citizen participation.; Land use -- South Africa -- KwaZulu-Natal -- Planning -- Citizen participation.; Conservation of natural resources -- South Africa -- KwaZulu-Natal -- Citizen participation.